Smkdiy attendance management system with sms service - Nurul Fatehah, Sulaiman (2013)
SMKDIY Attendance Management System with SMS Service (SMKDIY AMSSS) is build to facilitate the attendance management system in Sekolah Menengah Kebangsaan Dato’ Ibrahim Yaacob (SMKDIY) that are still using manual system. Manual attendance system left a lot of holes in effectiveness. Missing records, papers consumption and tardy reports are some of the obvious one. Student’s truancy is one of the indirect results from the current system. Hence, this system existed to convert all the manual system to a computerize one. Other than that the system also can provide SMS alert and generate informative reports for school monitoring. Prototype model is used for the development of the system as the model can elicit user’s requirements faster, and can detect defects earlier thus reducing the time and cost. For the development PHP language is used, and for the database is mySQL. Meanwhile for the hardware, Adobe Dreamweaver CS4 and Android SDK are employed for the web based and mobile based system. After completion, the system consists of a web based, a mobile application and SMS services. It is successfully used to facilitate attendance management by making the process faster, easier date retrieval and also ease the usage of paper in the office.